2019
DOI: 10.1016/j.engstruct.2018.10.044
|View full text |Cite
|
Sign up to set email alerts
|

The bond behaviour of CFRP-to-steel bonded joints with varying bond properties at elevated temperatures

Abstract: The mechanical properties of different adhesives at elevated temperatures can change differently due to the differences in adhesive molecular chain structure. Therefore, a profound understanding of the effect of these property changes on the bond behaviour of carbon fibre reinforced polymer (CFRP)-to-steel bonded joints is of great importance when designing bonded CFRP strengthening systems for steel structures. Existing studies on CFRP-to-steel bonded joints under monotonic loading have clearly shown that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…Furthermore, He, et al [11] exposed the specimens for 160 min at temperatures ranging from 23 • C to 75 • C. The degradation of the adhesive elastic modulus led to a reduction in bond strength by 10% at T g − 15 • C and 70% when T g +15 • C. However, Chandrathilaka, et al [12] tested eighty-two CFRP/steel double strap joints and reported that the reduction of bond strength, Poisson's ratio and elastic modulus of CFRP/steel joint occurred in a similar manner. Chandrathilaka, et al [13] also found that, despite the type and thickness of CFRP, an elevated temperature caused the initial softening of the bond and substantially lowered the shear stress to 10 MPa when the temperature exceeded 90 • C. Similar behavior was observed by Zhou, et al [14], who found that the elastic modulus and initial stiffness of the bond-slip curve and the peak bond shear stress deteriorated with increasing temperature. However, the total fracture energy increased when temperature is below T g and then decreased when the temperature exceeded T g .…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Furthermore, He, et al [11] exposed the specimens for 160 min at temperatures ranging from 23 • C to 75 • C. The degradation of the adhesive elastic modulus led to a reduction in bond strength by 10% at T g − 15 • C and 70% when T g +15 • C. However, Chandrathilaka, et al [12] tested eighty-two CFRP/steel double strap joints and reported that the reduction of bond strength, Poisson's ratio and elastic modulus of CFRP/steel joint occurred in a similar manner. Chandrathilaka, et al [13] also found that, despite the type and thickness of CFRP, an elevated temperature caused the initial softening of the bond and substantially lowered the shear stress to 10 MPa when the temperature exceeded 90 • C. Similar behavior was observed by Zhou, et al [14], who found that the elastic modulus and initial stiffness of the bond-slip curve and the peak bond shear stress deteriorated with increasing temperature. However, the total fracture energy increased when temperature is below T g and then decreased when the temperature exceeded T g .…”
Section: Introductionsupporting
confidence: 53%
“…The present study was exposed under service temperatures for seven continuous days prior to testing to demonstrate environmental exposure on the CFRP-strengthened steel structures. Meanwhile, the existing studies that show a reduction in strength were exposed to short-term service temperatures, ranging from just 15 min to 120 min [15,39]. The increase in ultimate strength at service temperature has revealed that the transformation of the adhesive matrix at service temperature does not reduce the bond strength but enables the further enhancement of the interfacial bonding between the steel, CFRP and adhesive interfaces and thus, improves the overall bonding performance.…”
Section: The Effect Of Service Temperature Cfrp Layers and Bond Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The FRP-strengthened beams in service are likely to experience significant temperature variations due to the daily and seasonal temperature changes (Al-Shawaf, 2010; Bai et al, 2021; Biscaia, 2019; Mhanna et al, 2020; Sahin and Dawood, 2016; Stratford and Bisby, 2012; Teng et al, 2021) and possible fire exposure (Gao et al, 2018; Kodur and Naser 2018; Kodur et al, 2019; Ouyang et al, 2021; Song et al, 2021; Yu and Kodur 2014). The temperature variations (i.e., thermal loadings) have two different effects on the interfacial behavior and the associated debonding failure: (a) thermal stresses at the FRP-to-steel/concrete interface that are induced by different thermal expansion coefficients of the FRP plate and the steel or concrete substrate (e.g., Gao et al, 2012; 2015a; Jia et al, 2021; Silva and Biscaia, 2008); (b) bond degradation of the FRP-to-steel/concrete interface due to the temperature-induced changes in the mechanical properties (e.g., strength and stiffness) of the bonding adhesive (e.g., Dai et al, 2013; Kodur et al, 2019; Zhou et al, 2019). It is noteworthy that the effects of thermal loadings on the mechanical properties of the reinforcing fibers of the FRP plate as well as the steel/concrete substrates are negligible (Nguyen et al, 2011; Sauder et al, 2004) compared with those of the bonding adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…The stress concentration at the ends of the overlap can be reduced by increasing the overlap length up to a certain magnitude, beyond which, it no longer has an effect [18]. Hao et al [19] investigated the behavior of CFRP-steel bonded joints at elevated temperatures, where significant effects of temperature-dependent bond-slip relation were observed under mode II loading. Li et al [11] studied pre-preg bonded composite single-lap joints.…”
Section: Introductionmentioning
confidence: 99%